Short implants (6 mm) installed immediately into extraction sockets: An experimental study in dogs - Bressan, Eriberto; Sivolella, Stefano; Almagro Urrutia, Zoraya; Salata, Luiz Antonio; Lang, Niklaus Peter; Botticelli, Daniele (Wiley-Blackwell, 2012)
Aim: To evaluate the effect of implant length (6 mm vs. 11 mm) on osseointegration (bone-toimplant contact) of implants installed into sockets immediately after tooth extraction.Material and methods: In six Labrador dogs, the pulp tissue of the mesial roots of P-3(3) was removed and the root canals were filled. Flaps were elevated bilaterally, the premolars hemisectioned and the distal roots removed. Recipient sites were prepared in the distal alveolus and a 6 mm or an 11 mm long implant was installed at the test and control sites, respectively. Non-submerged healing was allowed. After 4 months of healing, block sections of the implant sites were obtained for histological processing and peri-implant tissue assessment.Results: No statistically significant differences were found between test and control sites both for hard and soft tissue parameters. The bone-to-implant contact evaluated at the apical region of the implants was similar as well. Although not statistically significant, the location of the top of the bony crest at the buccal aspect was more apical in relation to the implant shoulder at the test compared with the control sites (2.0 +/- 1.4 and 1.2 +/- 1.1 mm, respectively).Conclusions: Shorter implants (6 mm) present with equal osseointegration than do longer implants (11 mm).
Keywords: animal study; extraction socket; implant dentistry; short implants; hard tissue; soft tissues; peri-implant mucosa; osseointegration